2008
DOI: 10.1002/anie.200704092
|View full text |Cite
|
Sign up to set email alerts
|

Multiple CH Activations To Construct Biologically Active Molecules in a Process Completely Free of Organohalogen and Organometallic Components

Abstract: Step by step: Highly selective cross dehydrogenative arylation of acetanilides was developed to construct biaryls under mild condition. With this method, different aryl CH bonds were activated in sequential reactions to construct functionalized carbazoles (see scheme), which are present as key structural units in various biological molecules and organic optical materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
96
0
5

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(101 citation statements)
references
References 63 publications
0
96
0
5
Order By: Relevance
“…[2] In recent years, the coupling of two aryl C À H bonds for the synthesis of an arene-arene linkage has witnessed remarkable progress. [3] In a challenging fashion, we recently reported the direct cross-coupling of an unactivated arene C À H bond with a cyclic alkane to produce a new Csp 3 À Csp 2 bond. [4] On the other hand, there are reported methods for the carbonylation of arene compounds but they are often limited by the prefunctionalization of the substrates or by the necessity to handle toxic carbon monoxide gas.…”
mentioning
confidence: 99%
“…[2] In recent years, the coupling of two aryl C À H bonds for the synthesis of an arene-arene linkage has witnessed remarkable progress. [3] In a challenging fashion, we recently reported the direct cross-coupling of an unactivated arene C À H bond with a cyclic alkane to produce a new Csp 3 À Csp 2 bond. [4] On the other hand, there are reported methods for the carbonylation of arene compounds but they are often limited by the prefunctionalization of the substrates or by the necessity to handle toxic carbon monoxide gas.…”
mentioning
confidence: 99%
“…We wondered therefore if established methods for the introduction of indoles onto other types of C-H bonds could be used to access products 13a and 15a. However, when reported methods for C-H indolation based on oxidative C-H/C-H couplings [24][25][26] with indole 8a or C-H functionalization with electrophilic indoles 16, 17 and 18, [18] were examined, compounds 13a and 15a could not be obtained (Scheme 2B). Therefore, the discovery of Indole-BX reagents allowed new C-H functionalizations which were not possible before.…”
Section: Methodsmentioning
confidence: 99%
“…The Shi group applied the Buchwald process to access 4-deoxycarbazomycin B, [41] a precursor to the carbazole antibiotic carbazomycin B, in just three steps in 32 % overall yield. The Inamoto group showed that the combination of a palladium(II) salt and an oxidant could be used to catalyze a variety of oxidative arene amidation to enable the synthesis of indoles [42] and quinolinones.…”
Section: Amines With Acidic Hydrogensmentioning
confidence: 99%